Effects of silvopastoral areas on dual-purpose cattle production at the semi-humid old agricultural frontier in Central Nicaragua - Yamamoto, Wataru (2004)
Tesis (Doctorado) -- CATIE. Escuela de Posgrado, Turrialba (Costa Rica), University of Wales, Bangor, UK, 2004